2019
DOI: 10.1353/cpr.2019.0043
|View full text |Cite
|
Sign up to set email alerts
|

Engaging African American Men as Citizen Scientists to Validate a Prostate Cancer Biomarker: Work-in-Progress

Abstract: Background African American men (AAM) are underrepresented in prostate cancer (PCa) research despite known disparities. Screening with prostate-specific antigen (PSA) has low specificity for high-grade PCa leading to PCa over diagnosis. The Prostate Health Index (PHI) has higher specificity for lethal PCa but needs validation in AAM. Engaging AAM as citizen scientists (CSs) may improve participation of AAM in PCa research. Objectives Assess feasibility of mobilizing CSs to recruit AAM as controls for PHI PCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…While community-based participatory research, citizen scientists’ engagement, and social network theory have all proven utility when deployed individually in the engagement of black men in research, the combined “triad” approach may prove a novel collaborative model that can address the multiple factors that impact the equitable engagement of black men in research. The “triad” model of engagement proved successful in a previous prostate cancer screening project to validate a new biomarker for prostate cancer screening, and has the potential to prove feasible in engaging black men in lung cancer screening (Watson et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While community-based participatory research, citizen scientists’ engagement, and social network theory have all proven utility when deployed individually in the engagement of black men in research, the combined “triad” approach may prove a novel collaborative model that can address the multiple factors that impact the equitable engagement of black men in research. The “triad” model of engagement proved successful in a previous prostate cancer screening project to validate a new biomarker for prostate cancer screening, and has the potential to prove feasible in engaging black men in lung cancer screening (Watson et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The concept of black men in America "reclaiming" their citizenship and identity as an active voice in research, and engagement is an important step in addressing the historical misgivings of black men and biomedical research. For example, in the pilot study engaging black men as citizen scientists to advance prostate cancer research, the cohort of eight black men engaged as citizen scientists all had elevated medical mistrust, but it was also noted that they welcomed an opportunity to engage with other black men in research (Watson et al, 2019). Engaging black men as citizen scientists may inform USPSTF evidence-based lung cancer screening guidelines and improve screening rates, by engaging black men in all aspects of the lung cancer screening process.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the articles exhibits successes and opportunities for further growth. Some of these articles, for example, the articles contributed by Matthews et al 1 and Watson et al, 2 showcase the true benefit of reaching out and partnering with communities and groups that traditionally have not been allowed to sit at the table with scientists, educators, and other academic partners. Collectively, the articles in this special issue demonstrate how ChicagoCHEC has embraced the goals of the funding announcement, not only by building cancer research capacity at the participating ISUPs, but also by conducting timely and original research aimed at reducing cancer health disparities.…”
Section: This Supplement To Progress In Community Health Partnershipsmentioning
confidence: 99%
“…1 Magasi et al 5 created community-tailored breast cancer screening messaging for members of the disability community. Watson et al 2 showed that empowering African American men to not just partner with a research team, but to substantially engage in the research as citizen scientists is another strong example of breaking the routine, community-engaged business as usual research partnerships and elevating partners’ status to scientists rather than just community partners. Sanchez- Johnsen et al 6 highlight the importance of understanding Latino men’s perceived body images to better inform the design of interventions to lower obesity.…”
Section: This Supplement To Progress In Community Health Partnershipsmentioning
confidence: 99%